Sleep duration and mental health in middle-aged and older adults: a study on gender differences - Jie Meng; Dan Li; Feng Sun; Lingling Tang; Jing Wang; Hui Li; Hui Li (Frontiers in Psychiatry)
BackgroundAs the global population ages, mental health issues among middle-aged and older adults have become an important public health concern. Although the impact of sleep disorders on mental health is widely recognised, the specific mechanisms underlying the gender differences in mental health among middle-aged and older adults due to differences in sleep duration remain unclear. This study aims to explore the impact of sleep duration on mental health differences between middle-aged and older adults of different genders, providing key mechanistic evidence for understanding gender inequality in mental health among middle-aged and older adults.MethodsA total of 5 743 middle-aged and older people aged 45 years and above were surveyed. The 10-item Kessler Psychological Distress Scale (Kessler10) was used to evaluate mental health status. A self-designed questionnaire was used to collect information on participants’ socio-demographic characteristics, physical health status, and daily lifestyles. A multiple linear regression model was adopted to analyze the effect of sleep duration on mental health, and then the Oaxaca-Blinder decomposition for linear model was used to further explore the effect of sleep duration on gender differences in mental health.ResultsThe scores of mental health scale of male and female participants were 12.16(4.19) and 12.53(4.31), respectively. The regression result showed that sleep duration had a significant impact on the mental health status of different gender participants, with a stronger effect observed in females. Furthermore, the Oaxaca-Blinder decomposition indicated that approximately 20.57% of the mental health differences could be attributed to gender differences in sleep duration.ConclusionsFemale middle-aged and older residents have poorer mental health compared to male residents. Moreover, the difference in sleep duration is an important component of the mental health gap between middle-aged and older people of different genders. These findings highlight the importance of improving the sleep quality of female residents in alleviating mental health issues among middle-aged and older adults, providing scientific evidence for the development of more gender-sensitive intervention strategies.